Evaluation of Spring Season Local and Improved Rice Genotypes on Growth, Yield, and Yield Attributing Characters in Gorkha District, Nepal - Acharya , Shreeja; Ghimire, Sudip; Thapa, Roshan; Bhattarai , Prakriti; Chhetri, Bidhya Poudel; Gautam, Bibek (Journal La Lifesci, 2024)
Rice cultivation faces challenges related to varietal selection, limiting the potential yield of spring rice crops. This study was conducted in the Rice Zone of Gorkha, Nepal during the spring season of 2022 with aim to evaluate the growth, yield, and yield attributing characters of different rice genotypes. The study hypothesized that significant differences exist among different rice genotypes in terms of their growth, yield, and yield attributing characters. The experiment employed a one-factor randomized complete block design (RCBD) with seven genotypes, including local varieties (Hardinath Hybrid 1, Chaite-5, CH 45, Salijudi) and pipeline genotypes (IR16L1919, IR10N118, IR86515), and replicated three times. Results indicated significant variations among genotypes in response to similar growing conditions and nutrient availability. Notably, CH 45 exhibited the highest plant height (113.50 cm), while IR16L1619 demonstrated the longest panicle length (28.56 cm) and the highest number of effective tillers (23.10). IR16L1619 also displayed the highest number of leaves (97.27 leaves) and leaf area index (8.00). Chaite-5 had the longest flag leaf (33.13 cm), while IR16L1619 recorded the highest panicle length (28.56 cm) and number of grains per panicle (270.10). Salijudi exhibited the lowest sterility percentage (7.52 %), and CH 45 displayed the highest thousand grain weight (26.40). Moreover, IR16L1619 demonstrated superior performance in terms of grain yield (8.19 t/ha), straw yield (7.12 t/ha), and biological yield (15.25 t/ha). The findings underscored the genotype-specific responses to environmental conditions, highlighting the importance of tailored varietal selection for optimal productivity.